GENDER, PATRIARCHY, AND THE ECONOMIC OPPRESSION OF WOMEN IN CHARLOTTE PERKINS GILMAN’S THE YELLOW WALLPAPER - Bilawal Bashir; Nomee Mehmood (International Journal of Contemporary Issues in Social Sciences, 2024)
The Yellow Wallpaper by Charlotte Perkins Gilman unveils an assertion of the role of women, and the domination of men in the late nineteenth century. By focusing on the life of the nameless female protagonist, who struggles with postpartum depression, the novella exposes the dangers of gender roles and medical authority. Physician-husband’s enforced ‘rest cure’ that mirrors contemporary patriarchal beliefs about women’s physical and mental weakness results in the protagonist’s mental decline. This paper discusses how Gilman employs the main character’s imprisonment, financial enslavement, and final slip into insanity as a commentary on the oppressive structures in society that oppress women. According to the principles of the feminist approach to literature, the work reconstructs the relationships between gender subordination, medical discourse, and economic exclusion. The wallpaper itself becomes a powerful symbol of the main character’s mental imprisonment and rebellion, referring to present women’s emancipation fight against the patriarchal world.